Unmanned ground vehicle for snow cover survey in avalanche areas using GPR - Sidorenko Artem; Moskvitin Alexander; Kondrashova Elena (E3S Web of Conferences)
The paper presents a concept for a ground-based unmanned automated tracked platform designed for the remote survey of snow cover using ground-penetrating radar in hazardous areas, such as avalanche catchment zones. Traditional observation methods, such as snow surveys and pit studies, are prohibited in these areas for safety reasons. Employing an alternative approach—ground-penetrating radar combined with an unmanned automated platform—enables safe research in avalanche catchment zones while covering extensive territories in a short period. The ground-based unmanned automated tracked platform comprises an autonomous tracked module connected by a variable-width frame designed for mounting the ground-penetrating radar. The modular technology allows the platform to be divided into two autonomous devices, facilitating movement in hard-to-reach areas, such as forests, shrub vegetation, and mountain ranges, during transportation from the foot of the avalanche basin to the study area.